Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1470773084 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Animalia" ] } The dataset includes 1470773084 records from 27868 constituent datasets: 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 31487 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 12 records from The fossil record of the family Benthopectinidae (Echinodermata, Asteroidea), a reappraisal. 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 5418 records from Données des membres de l'Association française d'Arachnologie. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 30 records from Artenvielfalt des "Grünen Klassenzimmers". 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 2814 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 32 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 14 records from An annotated checklist of Ciidae (Coleoptera: Tenebrionoidea) of Iran. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 5484 records from MCP-Aves - Coleção de Aves. 76 records from Notes On Some Fulgoroidea Of Guam. 74 records from Área ocupada por especies de fauna en el Parque Nacional Natural Selva de Florencia en el 2018. 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 51 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 76704 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 2 records from Carnivores of Syria. 1013 records from Vertebrados terrestres de San Juan de Camarones, Durango. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 304 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 8 records from The Indigo Project: a global citizen science Ocean survey. 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 3 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 3104 records from Collections of Bioclass, school #179, Moscow. 872206403 records from EOD – eBird Observation Dataset. 579 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 14 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 1818 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 206 records from Gross body measurements of Antarctic Rock Cod (Trematomus bernacchii) collected at sites adjacent to Casey Station 2012/13. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 282 records from Middlebury College Bee Collection. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 9120 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 8 records from Benthic macrofauna abundance of sediment core 12930-063. 13 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 13 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 218 records from Données naturalistes de Ingénieurs écologues GEREA. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 8 records from sediment metagenome Metagenome. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 18 records from Naturtag. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 193 records from A Compendium Of Distributional Records For Oroperla Barbara Needham, 1933 (Plecoptera: Perlodidae), With Additional Documentation Of Reproductive Morphology And Biology. 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 207 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 26 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 21 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 8 records from Pollen profile 2 from Richland Creek. 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 1913 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 13 records from Steinbruch Mainz-Weisenau, 4.Jahr. 12859 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17155 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 113502 records from TNHC Herpetology Collection. 354 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 278310 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 224419 records from Ocean Salmon Program - Barkley Sound Juvenile Salmon Study from 1987 to 1994. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 184 records from NMML Killer Whale Vessel, Bering Sea, 1992. 147 records from Cochlostoma revised: the subgenus Clessiniella Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 44 records from MIRC KB23 Shoreline Surveys May 2013. 270 records from bmhs_weatherheadshell_collection. 57898 records from Fichier communal des ongulés. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 4298 records from ColRest_Raw1. 19 records from A new species of Panaqolus (Siluriformes: Loricariidae) from the rio Madeira basin with remarkable intraspecific color variation. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 3 records from A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae). 57 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 19 records from Universidad de San Carlos de Guatemala - Colección de Equinodermos. 5678 records from SNH Bat Casework records 1970-2007. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 215 records from Living Cirripedia. 4 records from Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 1283 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 94968 records from flora&fauna(NIBR)2019. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 222 records from Land and freshwater molluscs of Northern Spain. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 13038 records from University of Nebraska State Museum Birds Collection. 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 31961 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 629 records from Occurrence of bird species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 463 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 3 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 20170 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 1 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5246 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 4 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 9 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 10 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 142 records from Hartland Nature Club Lepidoptera Collection. 114 records from BIRDRACE LiLaLau. 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 136549 records from Fish specimens of Kagoshima University Museum. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13649 records from UTEP Invertebrates (Arctos). 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 1308 records from Fish occurrence in Kuban River basin. 107 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 5 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 691 records from Tentaculata collection of National Museum of Nature and Science. 4 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 4 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 5 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 1 records from A new species of the genus Protoplotina Miyatake (Coleoptera: Coccinellidae) from India. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 11 records from Gulf of Maine Razorbill Tracking (aggregated per 1-degree cell). 8571 records from MfN - Mallophaga Collection. 201 records from An overlooked diversity-the Costellariidae (Gastropoda: Neogastropoda) of the Miocene Paratethys Sea. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 4 records from Dragmaxia anomala sp. n. (Demospongiae: Halichondrida) from the southwestern Atlantic (Brazil). 13 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 18 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 138 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 8 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 156 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 7 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 2316 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 3034 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 830955 records from AMNH Bird Collection. 21 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 2721 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 59 records from Seven new giant pill-millipede species and numerous new records of the genus Zoosphaerium from Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae). 4 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from the foothills of the Serranía de San Lucas, Norosí-Colombia. 6 records from Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 927 records from BioBlitz Barcelona 2010-14. 4 records from Nueva especie de Kessleria Nowicki, 1864 para Chile central (Lepidoptera: Yponomeutidae) asociada a Maytenus boaria Molina (Celastraceae). 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 18 records from Phase 2 Lowland Grassland Survey of Wales. 27 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 276501 records from hymenoptera. 466 records from FFH-Gebiet "Calwer Heckengäu". 372 records from Amphibian and Reptilian (KIEE-AR). 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 18 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 1287 records from Birds - Wild Birds (KIDR-BI). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 139 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 55 records from The Genus Daspletis Loew, 1858 And The Description Of Two New Genera, Anasillomos And Remotomyia (Diptera: Asilidae: Stenopogoninae). 27 records from Partial revision of the genus Robinsonia Grote 1866: description of five new species for the Neotropical fauna (Lepidoptera, Erebidae, Arctiinae, Phaegopterina). 4 records from A new rotifer species: Lecane langsenensis n. sp. (Rotifera: Monogononta) from Vietnam. 81532 records from Bob Merritt Coleoptera Dataset. 41100 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 12 records from Happywhale - Indian humpback dolphin in Indian Ocean. 13768 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 1043909 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 413272 records from DATAVES. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 109 records from Projet Diable de mer - AILERONS. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 591 records from Alan Wormington Collection. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1513 records from M. Gollop Collection. 53424 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 8 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 85 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 174 records from BIRDRACE Bon(n)apartemöwen. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 17 records from Plant-parasitic nematodes of Republic of Karelia. 2 records from Taxonomic notes on the genus Hydrobaenus with description of H. simferopolus sp. nov. from Crimea (Diptera: Chironomidae). 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 256 records from Herpetofauna asociada a ecosistemas de Buenaventura, Valle del Cauca. EPA-IIAP 2019. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 18939 records from Cowan Tetrapod Collection - Mammals. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 1 records from The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean. 20 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 39 records from Pollen profile ADR309. 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 16 records from Insect Collections of Okomu National Park- Nigeria. 215 records from Heinersdorfer Sumpfwiese. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 291402 records from ARABEL - Arachnologia Belgica. 2872 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 71 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 2 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 348 records from Antarctic pycnogonids. 2 records from A new country record of Raorchestes cangyuanensis Wu, Suwannapoom, Xu Murphy & Che 2019 and additional record of Kurixalus yangi Yu, Hui, Rao & Yang 2018 (Anura: Rhacophoridae: Rhacophorinae) from India. 1 records from Tyrannosaurus was not a fast runner. 62797 records from MLZ Bird Collection (Arctos). 15 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 2 records from Happywhale - False Killer Whale in South Atlantic Ocean. 2 records from Malgacheliodes martensi spec. nov. (Acari, Oribatida, Licnodamaeidae) from South Africa. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 9120 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1320 records from Ornithologie Federsammlung - SNSD. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 8 records from Priocharax nanus, a new miniature characid from the rio Negro, Amazon basin (Ostariophysi: Characiformes), with an updated list of miniature Neotropical freshwater fishes. 72 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 1 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 175 records from The Brown University Foraminiferal Data Base (BFD). 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 1 records from Anteon hubeni a new species from Ecuador (Hymenoptera: Dryinidae). 889 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 2 records from Perscheloribates Paratzitzikamaensis N. Sp., With Supplementary Descriptions Of Scheloribates Elegans And Monoschelobates Parvus (Acari, Oribatida, Scheloribatidae) From Ecuador. 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 135 records from Données naturalistes de Xavier BONNET. 330046 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 1015 records from Programme ACT : Répartition Merle noir 2005 - 2009 Coordonnées GPS Lambert 93. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 8 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 1233 records from Some finds of flora and fauna in Kharkiv region. 3 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 130 records from Vamize and Ibo islands corals dry collection MHNM. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 14 records from Collection Amphibia fossil SMF. 22 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 8835 records from Données naturalistes de Benoit MARTHA. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 6 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 55048 records from Observations occasionnelles Parc national des Pyrénées. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 3 records from Molecular phylogenetics, PCA, and MFA recover a new species of Cyrtodactylus (Squamata: Gekkonidae) from an isolated sandstone massif in northwestern Cambodia. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 3 records from Cosmocerca acanthurum n. sp. (Nematoda: Cosmocercidae) in Pseudoeurycea leprosa and Chiropterotriton orculus from the Transmexican Volcanic Belt, Central Mexico, with a checklist of the helminth parasites of plethodontid salamanders. 316 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 3 records from Microlaimus capitatus sp. n. and Dichromadora simplex Timm, 1961 (Nematoda, Chromadorea) from the coast of Vietnam. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 24 records from The geometrid moths of Ethiopia I: tribes Pseudoterpnini and Comibaenini (Lepidoptera: Geometridae, Geometrinae). 14 records from First study of the Polycladida (Rhabditophora, Platyhelminthes) from the Pacific Coast of Costa Rica. 112 records from Antarctic Pycnogonids II. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 19 records from Review of the dwarf Glossogobius lacking head pores from the Malili lakes, Sulawesi, with a discussion of the definition of the genus.. 6979 records from Upper Silesian Museum, Bird Observations. 149 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 269 records from SEWBReC Springtails and allies (South East Wales). 5 records from Morphological and molecular description of a new genus and species of black coral (Cnidaria: Anthozoa: Hexacorallia: Antipatharia: Antipathidae: Blastopathes) from Papua New Guinea. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 28745 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 59 records from Artenvielfalt auf dem Schulgelände. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 5 records from New data on the oriental Xantholinini. 36. Description of the male of Thyreocephalus elegantissimus BORDONI, 2012 and new records (Coleoptera, Staphylinidae) 253 ° contribution to the knowledge of the Staphylinidae. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 187 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Données de la naturaliste Laurence Beauchamp. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 123 records from Ladybirds of Ireland. 7 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 16 records from Données naturalistes de ROLLAND Blandine. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 436 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 32 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6192 records from NE Scotland fish records 1800-2010. 3 records from Distribution Of Moselia Infuscata (Claassen, 1923) (Plecoptera: Leuctridae) In Canada. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 3 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 2 records from Perotrochus caledonicus (Gastropoda: Pleurotomariidae) revisited: descriptions of new species from the South-West Pacific. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 412 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 26 records from Liether Park (LMS), 5a. 6672 records from Midden-Limburg Fish Ponds Survey. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 8 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 2 records from Leiner-Herbar Konstanz. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 144 records from Cactophilic Drosophila and Opuntia. 105 records from bmhs_moth_collection. 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 20 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 836 records from SEFSC GoMex Oceanic 1993 (W). 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 44709 records from WCPS Bird Survey Project. 92 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 106 records from Sylter Meerstrandläufer. 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 8 records from Complementary description of Podocinella misella (Berlese, 1913) (Acari: Podocinidae) and a key to world species of the genus. 1 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1290 records from Diversity of Spiders from Azorean Trails. 13442 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 69 records from Pollen profile RAC20, Lake Racou, France. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 9150 records from NEON Biorepository Carabid Collection (DNA Extracts). 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 28 records from Données naturalistes de Franck MERLIER. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 9201 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 2556 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 470 records from Gross body measurements of Laternula elliptica collected from sites adjacent to Casey Station 2014/15. 12 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 20 records from Données naturalistes de LE GLOANEC Vincent. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 29 records from Oberes Schindelbachtal. 213433 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 1 records from Juvenile eucladid crinoid from the Middle Devonian of Turkey. 104 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 7122 records from Whale catches in the Southern Ocean. 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 6 records from A new Synbranchus (Teleostei: Synbranchiformes: Synbranchidae) from ilha de Marajó, Pará, Brazil, with notes on its reproductive biology and larval development. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 2 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 230 records from Biometría peces Parque Nacional Natural La Paya. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 12 records from New or rare Madagascar tiger beetles- 20. Pogonostoma (Bathypogonum) horimichioi sp. nov. and supplemented characters of P. (B) levigatum levigatum (W. Horn) and P. (B.) levigatum lucens Rivalier (Coleoptera: Cicindelidae). 1079 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 32 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 13846 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 3 records from New early Pleistocene Alligator (Eusuchia: Crocodylia) from Florida bridges a gap in Alligator evolution. 11 records from Benthic macrofauna abundance of sediment core 13077-063. 24 records from Taxonomic revision of Australian Amobia Robineau-Desvoidy, 1830 (Sarcophagidae: Miltogramminae): integrating morphology and genetics finds a new species and tackles old problems. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 28 records from (Table 4) New palynological record of sediments from Odderade. 14 records from Protist Diversity in the East China Sea. 18 records from Anfibios presentes en el Cerro Jánano. 26 records from Données espèces - Expertise IPE 79. 1591319 records from NBIS Records to December 2016. 172 records from Nezara viridula records held by the Royal Horticultural Society. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 128 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 1511 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 796 records from Occurrence of insect species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 688 records from South American Antarctic Marine Biodiversity Literature. 1 records from Redescription of Corydoras guapore Knaack, 1961 (Siluriformes: Callichthyidae), a midwater Corydoradinae species from the rio Guaporé basin. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 4 records from Happywhale - in South Atlantic Ocean. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 4463 records from California State University, Long Beach Birds. 2 records from The origin and evolution of the Tyrannosaurids, Part 1. 1926 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 33 records from Occurrence of mammalia relicts at site Sveduv stul. 194618 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 9 records from Molecular circumscription of new species of Gyrocotyle Diesing, 1850 (Cestoda) from deep-sea chimaeriform holocephalans in the North Atlantic. 332 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 20576 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 89 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 3764 records from Swiss National Cicadidae Databank. 7148 records from DMNS Egg Collection (Arctos). 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 144 records from Colección de moldes endocraneanos del CENPAT. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 4 records from Two new sympatric species of Eusarsiella (Ostracoda: Myodocopida: Sarsiellidae) from the Florida Keys with a morphological phylogeny of Sarsiellinae. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 16 records from A new species of Neoliomera Odhner, 1925, from the western Pacific, and the first record of N. demani Forest & Guinot, 1961, from Taiwan (Crustacea: Decapoda: Brachyura: Xanthidae). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 2112 records from Study on plankton at the port of Ostend in 1965. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 28 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 11 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 13 records from Eubria mesoamericana Barr and Shepard (Coleoptera: Psephenidae: Eubriinae), a New Psephenid Species from Central America with an Enigmatic Generic Distribution. 19 records from Distribution Data for Megachile chomskyi. 1012 records from Programme ACT : Répartition Merle noir 2011 - 2015 Coordonnées GPS Lambert 93. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 2 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 15 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 249 records from Fermanagh Flora. 80 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 464 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 3 records from Range table from benthic foraminifers in ODP Hole 149-900A. 1 records from On the Chilopoda from Turkey. 145 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservación Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 4 records from Proposal of Marbefia, gen. n. and Inermiphonte, gen. n., including updated keys to the species of Pseudonychocamptus Lang, 1944 and Paralaophonte Lang, 1948 (Copepoda, Harpacticoida, Laophontidae). 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 62055 records from UCLA Donald R. Dickey Bird and Mammal Collection. 5 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 5 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 15 records from Description of lithologic section units of IODP Hole 325-M0041A. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 2589 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 23 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 19619 records from Carabidae of the Carpathians. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8 records from An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792 - 1851). 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 15883 records from Canadian Lakes Loon Survey. 534 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 125 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 98 records from Données opportunistes sur les odonates. 74729 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 70 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 16758 records from Données Entomologiques A. HORELLOU 1988-2018. 77 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 284 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Тaxonomic position of Orthochirus olivaceus (Karsch, 1881), the type species of the genus Orthochirus Karsch, 1892 (Scorpiones: Buthidae). 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1895 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 1536 records from Records of Halicarcinus planatus at sub-Antarctic regions. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 56 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 34 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 42 records from Données espèces - Expertise IPE 37. 6 records from On the Chilopoda from Turkey. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from Maria Cleofas Island, Nayarit, Mexico. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 84 records from Ostracoda abundance of Hole 48-403. 77 records from Shannon Index and species richness for arthropods. 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 1 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 67 records from Monitoreo de la ocupación del Oso de antejoso (Tremarctos ornatus) en el Parque Nacional Natural Las Hermosas Gloria Castaño de Valencia para 2017 y 2018. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 2 records from Benthic foraminifera abundance of Hole 84-567A. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 9120 records from ICEL (Land - Invertebrates). 29033 records from UTEP Herpetology (Arctos). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2 records from The genus Lindaspio (Annelida: Polychaeta: Spionidae), and a new species from an oil field off Congo, western Africa. 107 records from Revision of the genus Miridiba Reitter, 1902 (Coleoptera, Scarabaeidae, Melolonthinae): genital morphotypes and new taxonomic data. 14964 records from Biological Reference Collections ICM-CSIC. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 349178 records from AMNH Herpetology Collections. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 723 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 137 records from Lynx 2011 présence Occasionnelle Maille 10km Réseau Loup-Lynx ONCFS. 69 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 48 records from Identification of Important Turtle Areas for green turtles in the Sulu Sulawesi Marine Ecoregion (aggregated per 1-degree cell). 2316 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 16 records from Phenological Center - Fishes (Murmansk). 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 245 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 6 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 14510 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 8704 records from HSU Wildlife Birds. 14 records from The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus). 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 247671 records from Odonata Central. 3408 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 33 records from Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners. 10098 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 2998 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 119382 records from Mammalogy Collection - Royal Ontario Museum. 10 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 2 records from Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger B (Apidae, Colletinae). 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 2 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 13 records from Contribution to the taxonomic knowledge of Ampharetidae (Annelida) from Antarctica with the description of Amage giacomobovei sp. nov.. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 5 records from CBCGDF CCAfa Volunteer Observation Archive. 18265 records from Levantamientos portuarios de fitoplancton, zooplancton, perifiton y macrozoobentos en el Pacífico colombiano. 35 records from Parascolopsis akatamae, a new species of dwarf monocle bream (Perciformes Nemipteridae) from the Indo-West Pacific, with redescription of closely related species P. eriomma. 43 records from Pelmatellus Amicorum Delgado And Ruiz-Tapiador (Coleoptera: Carabidae), A New Species From The Andean Altiplano Of Peru. 178459 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 2988 records from Données naturalistes d'Emmanuel SECHET. 310070 records from Seasearch Marine Surveys in England. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 25 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 155 records from HRC CRC Small Vessel-Based Monitoring Surveys March-April 2006. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 79 records from BIRDRACE Blinde Hühner. 13 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 4 records from Rhipidocotyle labroidei n. sp. (Digenea: Bucephalidae) from Labroides dimidiatus (Valenciennes) (Labridae). 5592 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 211 records from Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae). 1 records from A new species of bat of the Hipposideros bicolor group (Chiroptera: Hipposideridae) from Central Laos, with evidence of convergent evolution with Sundaic taxa. 19 records from Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 4 records from A new species of Sarcofahrtiopsis (Insecta, Diptera, Sarcophagidae) from mangrove forests in the Brazilian Amazon, with a key to species identification. 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 1083 records from Soil Invertebrates Surveys from the Chronicle of Nature of the Prioksko-Terrasnyi Biosphere Reserve. 5 records from Four new species records of Antennoseius and Anystipalpus (Acari: Mesostigmata: Ascidae) phoretic on Carabidae beetles from France. 1 records from Description of a new species of Neocordulia Selys, 1882 (Odonata: Libellulidae, Corduliinae) from southern Brazil. 137589 records from Arizona State University Hasbrouck Insect Collection. 4904 records from Mingan Island Cetacean Study 84-07. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 39 records from Integrating data to redescribe Euschistus taurulus Berg (Hemiptera: Pentatomidae). 40 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 8 records from A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae). 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3363 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 9 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 10 records from Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar. 27 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 13 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 198 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 628 records from SWFSC Marine Mammal Survey, Vaquita 1997, Cruise 1608. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 102 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 146 records from OCEAMM harbor porpoise sightings in the North Sea. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 5703 records from MICA - Muskrat occurrences collected by VMM in Flanders, Belgium. 4 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 10 records from Occurrence of mammalia relicts at site Dorog. 10217 records from Amphibian specimens of Tochigi Prefectural Museum. 7 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 4946 records from Harbour seal (Phoca vitulina) counts and haulout locations in the Strait of Georgia, British Columbia coast. 125 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 87546 records from MDFRC macroinvertebrate survey. 2 records from A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data. 1 records from Rhysacephala masneri n. sp. (Xiphydriidae), the first symphytan wasp recorded from Lord Howe Island. 6 records from Morphology of the males of seven species of Ortheziidae (Hemiptera: Coccoidea). 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 128 records from Inventaire des reptiles 2014. 8 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 2 records from Gladiopycnodontidae, a new family of pycnodontiform fishes from the Late Cretaceous of Lebanon, with the description of three genera. 2 records from Two new charismatic Pristimantis species (Anura: Craugastoridae) from the tepuis of “ The Lost World ” (Pantepui region, South America). 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 3 records from A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis. 2969 records from Cladocera distribution updates 2014. 6 records from Two new species of Lauratonema (Nematoda: Lauratonematidae) from the intertidal zone of the East China Sea. 77181 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 94 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 185 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 3 records from Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species. 6 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 25 records from Vom Wert alter Amateursammlungen - vier Spinnenarten neu für die Schweiz in der Sammlung Ketterer. 466 records from Northern elephant seals post-molting 2018 (aggregated per 1-degree cell). 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 2484 records from Museum TwentseWelle (NL) - Fossil Sponges Collection. 8 records from Marine Plants (NHMC-SA). 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 2 records from Studies in Neotropical Pseudophyllinae: A new genus of Cocconotini from the ColombianAndes and new subfamily assignment of the Dominican genus Anacaona (Tettigoniidae: Pseudophyllinae: Cocconotini). 67 records from Evaluación del efecto de esponjas arrecifales en el asentamiento larval de corales escleractinios. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 122 records from Scottish Beaver Trial incidental species records. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 54 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 3002 records from Colección de Peces Universidad Católica de Oriente. 1856 records from Données du naturaliste DELAPRE Jean-Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 11 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 1 records from The genus Alphocoris in the Indomalaya (Hemiptera: Heteroptera: Scutelleridae). 78 records from (Table 2) Sediment constituents and quartz in the sand-sized fraction, West Florida slope and Eastern Mississippi Fan, during USGS R/V Gyre cruises G80-6A and G81-8. 1 records from Hoplophora ardua. 140 records from Swedish Malaise Trap Project (SMTP) - Braconidae: Cheloninae: Adelius. 390 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE272. 14 records from Abundance of epibenthic echinoderms at seafloor photography station M21/4_250. 31 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 111 records from Birdrace-Uhulogen-Lippe. 106 records from Coloration variability of the Oriental genus Agnorimus Miyake & Iwase, 1991 (Coleoptera: Scarabaeidae, Cetoniinae) with synonymic notes. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 3 records from Analyses of the recent components of sediment core PS1400-4. 66 records from First catalogue of the Asopinae (Hemiptera, Pentatomidae) from French Guiana. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 3 records from Registros de la babilla (Caiman cocodrilus) asociados al Proyecto: Correlación entre nivel de testosterona, territorialidad y éxito reproductivo. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 39 records from Swedish Malaise Trap Project (SMTP) - Formicidae. 373 records from Otter survey of Ireland 2004 & 2005. 1528 records from Royal Belgian Institute of Natural Sciences Bryozoa collection. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 2 records from Species of the genus Chrysotus Meigen, 1824 (Diptera: Dolichopodidae) from Japan, with descriptions of two new species. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1359 records from Happywhale - Gray Whale in North Pacific Ocean. 124 records from Birdrace-LohmannsAdleraugen-Münster. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 267391 records from All taxa records for Leicestershire and Rutland. 139 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 137 records from Données naturalistes de NOËL Rémi. 6 records from First description of the male caste of the Himalayan endemic ant Lasius alienoflavus Bingham, 1903 (Hymenoptera: Formicidae), with re-description of the female and queen castes. 1998 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 307 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 1 records from La Côte oubliée - La Planète Revisitée - Nouvelle-Calédonie 2017. 17 records from Two new species of Balacha (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from Brazil with comments on their phylogenetic position and biogeography. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 3 records from Helobdella buzz n. sp. (Clitellata: Hirudinida), a bromeliad leech from the Brazilian Atlantic Forest. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tytonidae. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 9 records from A new genus and species of Oxycarenidae (Hemiptera, Heteroptera, Lygaeoidea) from Argentina. 1700 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 1 records from Taxonomic revision of the genus Lycenchelys (Osteichthyes: Zoarcidae) in Japanese waters. 42 records from A new species of the grass-feeding leafhopper genus Amblysellus Sleesman (Hemiptera: Cicadellidae: Deltocephalinae) from western Mexico, with a checklist and key to species. 31 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 401 records from Données de VINCENT Alexis (SAPROX). 286 records from Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 2 records from A new species of Symbiopsocus Li (Psocodea: “ Psocoptera ”: Psocidae) from Taiwan, China, with a revised checklist and key to species. 12 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 51 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 999991 records from Texas A&M University Insect Collection. 214 records from Insectarium René-Martineau (IRM). 134 records from Palynological investigation of profile Tso Kar. 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1015 records from Cepora butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 348735 records from KUBI Herpetology Collection. 179 records from Ictiofauna de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 62 records from Sibojaï_2017_12_18. 277 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 355 records from Meetnetten.be - Fyke counts for Amphibia in Flanders, Belgium. 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 37479 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 6630 records from Los mamíferos del estado de Durango, México. 14 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 104745 records from MSB Fish Collection (Arctos). 13 records from A contribution to the taxonomy of Anthaxia (Cratomerus) (Coleoptera Buprestidae: Anthaxiini) of East Africa. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 21032 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 158 records from Langes Tannen (Uetersen). 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 595 records from Churchyards for London. 2 records from Aktion des Romain-Rolland-Gymnasiums. 21 records from A new genus of Theraphosid spider from Mexico, with a particular palpal bulb structure (Araneae, Theraphosidae, Theraphosinae). 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 26 records from Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species. 710 records from Chronicle of Nature - Phenology of Fishes of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 36 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from New species and records of the pseudoscorpion genus Geogarypus (Pseudoscorpiones: Geogarypidae) from India, Sri Lanka and New Guinea. 1195 records from Edible Insects Collection of the Natural History Museum Bulawayo (NMZB), Zimbabwe Occurrence dataset. 19 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 55 records from Integrative taxonomy of Thalerosphyrus Eatonı 1881 (Ephemeropteraı Heptageniidae) in Thailand. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 3 records from Happywhale - Rough-toothed Dolphin in South Atlantic Ocean. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 5 records from A new species of Ashlockobius (Heteroptera: Rhyparochromidae: Myodochini) from Venezuela. 24 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 5 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 283 records from North Carolina Aquarium at Pine Knoll Shores Sea Turtle Awareness (aggregated per 1-degree cell). 12391 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 64 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1877 records from Odonata de la huasteca potosina (insecta). 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 2 records from Studies on the systematics and taxonomy of the genus Hylaeus F. (8) Revision of the Afrotropic subgenus Hylaeus (Deranchylaeus) Bridwell (Hymenoptera: Anthophila, Colletidae). 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 22 records from A new species and four new records of Diduga Moore (Lepidoptera, Erebidae Arctiinae) from Thailand. 175 records from PSUZC-Rodents Collection. 3 records from Zoology in the Middle East. 110 records from Données naturalistes de Mr MONTAGNER Sylvain. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68913 records from Données de l'Observatoire de la Faune de Bourgogne. 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 14 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 1015 records from Monitoreo de aves en la zona del Anchicaya (Colombia, Valle del Cauca, Buenaventura) en el marco del Convenio de Investigación Icesi/Celsia. 4447 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 5915 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 6 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 16 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 22 records from Redescription of the genus Koumansetta (Teleostei: Gobiidae), with description of a new species from the Red Sea. 1 records from First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 4 records from Analyses of the recent components of sediment core PS1011-1. 65 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 69 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 26 records from Schwedische Oribatei (Acari). III.. 1 records from Hypochthonius rufulus. 33 records from MVZ Herp Observations (Arctos). 154 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 2 records from A new species of the subgenus Tachycines (Tachycines) (Othoptera: Rhaphidophoridae) from Guizhou, China. 5 records from Polymetallic nodule field Targeted loci environmental. 50 records from (Table 1) Time series of ostracod population density off Bokniseck shore ('Hausgarten'), western Baltic Sea. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 2 records from Uncultured eukaryotes Targeted Locus (Loci). 58 records from (Table 1) Stratigraphic occurrence of selected diatom species from ODP Hole 105-647A. 13 records from Coleção de Coleoptera da Universidade de Brasília. 647 records from Twenty-two new species in the genus Hyphantrophaga Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, with a key to the species of Mesoamerica. 45 records from Herpetofauna de la expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 7 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 39 records from A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda). 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 1 records from Celaeno coccinea. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 202122 records from National Benthic Inventory. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 258 records from Fossil Specimens of Komatsu City Museum. 9 records from World’s northenmost and rarely observed Nudibranchs: three new Onchidoridid species (Gastropoda: Doridida) from Russian seas. 116 records from Programme ACT : Répartition Perdrix rouge 2004 - 2008 Coordonnées GPS Lambert 93. 1 records from Redescription of the poorly known pea crab, Pinnixa plectrophoros Glassell, 1935 (Decapoda: Pinnotheridae), from the Gulf of California. 37 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 1 records from Collection Quaternary Small Mammals IQW. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 4 records from The Chinese species of the genus Phlaeopterus Motschulsky, 1853 (Coleoptera Staphylinidae: Omaliinae: Anthophagini). 3327 records from BioGIS - Mammals - SPNI. 29 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 3586 records from Monitoring of the intertidal biodiversity of rocky beaches with schools in Portugal 2005-2010. 4 records from First report of the genus Tettigonia Linnaeus (Orthoptera: Tettigoniidae: Tettigoniinae) and record of Tettigonia caudata caudata (Charpentier, 1842) from India. 180 records from Colección Nacional de Lombrices de Tierra Universidad Tecnológica de Pereira (CNLT UTP). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 27 records from Colección Invertebrados-Museo de Historia Natural Unillanos. 8 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 58 records from The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae). 17 records from Neue Arten der Gattung Atomaria STEPHENS, 1830 aus der Türkei und dem Irak (Coleoptera, Cryptophagidae). 72 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 42415 records from MfN - Fossil vertebrates IV. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 2285 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 8 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 55019 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3483 records from Arthropod fauna in christmas tree plantations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6301 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 99 records from HRC CRC Small Vessel-Based Monitoring Surveys April-May 2008. 49 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 2 records from Extraordinary majoid crabs: the genus Esopus A. Milne-Edwards, 1875 in the new subfamily Esopinae subfam. nov., and erection of Paulitinae subfam. nov. (Crustacea, Decapoda, Brachyura, Majoidea, Inachoididae Dana, 1851). 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 72 records from Données du naturaliste Mael Garrin. 15 records from Two new species of the genus Sinotilla Lelej, 1995 (Hymenoptera: Mutillidae), with notes on taxonomic characters. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 59 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 12110 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates facula. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 12 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 171 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 1115 records from Données opportunistes sur les rhopalocères. 261 records from Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 7327 records from Pseudoscorpion Recording Scheme of the UK. 4 records from On two genera of spiny Pudicinae (Nematoda: Trichostrongylina) parasites of the spiny rat Proechimys simonsi (Mammalia: Echimyidae) from Peru. 34 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 39 records from Suivi des reptiles en forêt du Madrillet. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 12 records from A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions. 11241 records from Données du naturaliste DEHALLEUX Axel provenant de la base de donnée du SINP Île-de-France CETTIA. 1976 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 9 records from Cnidaria ZMK. 83180 records from Ground beetles (Carabidae) in urban habitats of Kaluga city (Russia). 145 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 1564 records from Leif Richardson Vermont Bee Specimens. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 1 records from Olga Lakela Herbarium, University of Minnesota Duluth. 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 44 records from Leegmoor (Moormerland/Leer). 34 records from Earthworms population in old-growth taiga forests of Pechoro-Ilych State Nature Reserve. 30879 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 9 records from Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 92 records from Ricinulei Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Taxonomic study of the genus Meganola (Lepidoptera, Nolidae, Nolinae), with three new species and a new record from China. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 7 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 47 records from Three new species and six new records of Scathophagidae (Diptera) from Japan with a key to the Japanese genera. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 11 records from New species of Rivudiva Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) with comments on R. minantenna Lugo-Ortiz & McCafferty and R. trichobasis Lugo-Ortiz & McCafferty. 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 342 records from Données opportunistes de Mammifères marins SPM de 1997 à 2007 récoltées par le RNE et le Baleineau de SPM de 1997 à 2007. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 5 records from Tyrannosaurus and other Cretaceous carnivorous dinosaurs. 10 records from A new species of Bomansius Lacroix (Coleoptera: Lucanidae) from Vanuatu, with redescriptions of its genus and its only congener, Bomansius gabrieli Lacroix, 1978. 30 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 3 records from Tracking rehabilitated green turtles from Mabul Island, Sabah, Malaysia (aggregated per 1-degree cell). 16603 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 632 records from Macro-invertebrates of the Desna river basin. 467 records from Noctuidae brasileiros de importancia economica depositados na coleção MNHUK. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 23 records from New synonyms of Euconnus (Tetramelus) kraussi Reitter, 1880 (Coleoptera Staphylinidae, Scydmaeninae). 23 records from The genus Arrhopalites (Collembola, Arrhopalitidae) in Asia, with the description of two new Japanese species of Yosiis collection. 10 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 441 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 7407 records from Dipterists Forum: Field Week 2018 (Stoke). 15491 records from Waterway Survey. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 6 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 7076556 records from Great Backyard Bird Count. 4 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 54 records from Notes on the genus Echinops L. (Asteraceae) in SE Europe. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 140 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 5759 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 9210 records from SuLaMa bird occurence data. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 3 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 15 records from New genus and species of Leptopsaltriini (Hemiptera: Cicadidae: Cicadinae) from China and Vietnam, with colour-changing behaviour reported for the first time in Cicadoidea. 58 records from Ostracoda abundance of Hole 42-372. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 170 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 3600 records from Amphibian and reptile records for Great Britain 2016-2019. 12 records from On the land snail Rhagada Albers, 1860 (Gastropoda: Camaenidae) from across the Lesser Sunda Islands. 356 records from Morphologische Daten von Puffinus creatopus. 272 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 5 records from Three Oriental species of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae) from China. 8 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 9084 records from WTSWW Data: All Taxa (West Wales). 20 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 19 records from Census of the fruit and flower chafers (Coleoptera, Scarabaeidae, Cetoniinae) of the Macau SAR, China. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 51 records from Regionalpark(Hattersheim). 124 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 26 records from A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894). 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 811 records from Revision of the Neotropical caddisfly genus Phylloicus (Trichoptera: Calamoceratidae). 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 47 records from Unter hellen Zinnen und finsteren Grotten. 72 records from A New Mormoopid Bat From The Oligocene (Whitneyan And Early Arikareean) Of Florida, And Phylogenetic Relationships Of The Major Clades Of Mormoopidae (Mammalia: Chiroptera). 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 4 records from Alien aquatic invertebrates of Republic of Karelia: Eriocheir sinensis (Edwards, 1853). 82436 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Feathers_and_Skin. 9 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 10269 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 221 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae Anthophagini) of the Iberian Peninsula. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 278 records from Gomex Sperm Whale Survey 2000. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 2350 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 12 records from Occurrence of mammalia relicts at site Niederlehme. 179 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 1264 records from Grand Voyeux - Suivis scientifiques. 86 records from UWIZM Cnidarians. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Integrative taxonomy at the nexus of population divergence and speciation in insular speckled rattlesnakes. 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 6 records from On the systematics of the water mites Hygrobates nigromaculatus Lebert, 1879 and H. setosus Besseling, 1942 (Acari, Hydrachnidia, Hygrobatidae). 87269 records from Taiwan Forestry Research Institute. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 178471 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40314 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 20196 records from UAM Invertebrate Collection (Arctos). 4 records from Discovery of the first pincer wasp (Hymenoptera, Dryinidae) from Rovno amber. 13 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 4 records from Review of Neoanchisquilla Moosa, 1991 and Neclorida Manning, 1995 (Crustacea: Stomatopoda: Squilloidea), with descriptions of two new species of Neoanchisquilla from the Indian Ocean. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 4 records from Arthropoden aus südostalpinen Höhlen.. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 12 records from Chronicle of Nature - Phenology of Amphibia of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 45 records from Brown bear monitoring data from Deosai National Park. 246 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 1632 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 10 records from A new Hasemania Ellis from the upper rio Paraná basin, with the redescription of Hasemania crenuchoides Zarske & Géry (Characiformes: Characidae). 1287 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 22 records from Megymenum tuberculatum, a new species of Megymenini from Java and a review of distribution of M. brevicorne (Hemiptera: Heteroptera: Dinidoridae). 160 records from Duck sightings per month, Macquarie Island. 99402 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 31 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 2741 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 446 records from Automatic acoustic Monitoring and Inventoring of BIODiversity. 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 33 records from Faunal assemblage of sediment core TR149-32. 31 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3113 records from Herpetile collection NTNU University Museum. 7 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 5 records from Warnowufer Groß Klein. 20 records from Heteroptera - SMNG. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 21 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 175 records from Revisión taxonómica de Pseudococcus Westwood (Hemiptera: Pseudococcidae) de Centro y Sud América con descripciones de especies nuevas. 1 records from A dryinid wasp in Early Eocene amber from the Paris basin (Hymenoptera: Dryinidae). 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 23226 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 124 records from Zur Taxonomie und Verbreitung einiger westpaläarktischer Arten der Gattung Planeustomus J V (Coleoptera, Staphylinidae, Oxytelinae). 78 records from (Table T2) Dinoflagellate stratigraphy of ODP Hole 184-1148A. 7 records from Two new Kukri Snake species (Colubridae: Oligodon) from the Nakhon Si Thammarat Mountain Range, and addition of O. ocellatus to the fauna of Thailand. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 835 records from SEFSC Caribbean Survey 2000. 24 records from Peces de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 639 records from Chronicle of Nature - Phenology of Mammals of State Nature Reserve Olekminsky. 22 records from TAMUG/NPS/NRDA Kemp's ridley nesters 2012 (aggregated per 1-degree cell). 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 6 records from Taxonomic revision of the genus Glenopopillia (Coleoptera: Scarabaeidae: Rutelinae). 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 1596 records from Parque Nacional Natural Sanquianga, monitoreo veda de camarón. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 54 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 39 records from Soolbach-Tal. 14 records from Description d'un nouvel Hipposideros (Chiroptera) de la Côte d'Ivoire.. 98 records from Registros de peces y cetaceos en el marco del proyecto Ocurrencia, distribución, estado genético y de contaminantes de los cetáceos de La Guajira. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 9 records from Extracellular DNA marine sediment Targeted Locus (Loci). 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 74 records from SuLaMa reptile monitoring. 2 records from Description of a new species of the genus Paraedes (Diptera: Culicidae) in Assam, India. 15 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 53 records from The vespid fauna of Pakistan. 1 records from A new reticulated beetle (Coleoptera: Cupedidae) from Mexico with a catalogue of Cupedidae species of the world. 1 records from Occurrence of mammalia relicts at site Ejstrup. 28382 records from Plan de vertebrados de la Patagonia. 13 records from A novel symbiotic relationship between mites and recluse spiders (Sicariidae: Loxosceles), with a description of a new Callidosoma species (Trombidiformes: Erythraeidae). 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 15 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 2 records from Occurrence of mammalia relicts at site Igstadt I. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 6187 records from Données naturalistes de Nathalie POT. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 34 records from Five new species and a new record of Sathytes Westwood from eastern China (Coleoptera: Staphylinidae: Pselaphinae). 65 records from Macrofauna abundance in surface sediment sampled during cruise DI226. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 35937 records from Biodiversity4all Research-Grade Observations. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 4 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 72 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 57286 records from Fish Specimens. 25 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 17917 records from NCSM Mammalogy Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 4 records from Two new species of the genus Scaphidium Olivier (Coleoptera: Staphylinidae Scaphidiinae) from Southwest China. 66 records from Amblyseius bellatulus Tseng (Acari: Phytoseiidae): neotype designation with first description of a male. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 57 records from Abundance of benthos infauna at station GIK23006-3. 225 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 32 records from Bat records from Nocturne Environmental Surveyors Ltd. 7 records from Plectranthias cruentus, a new species of anthiadine perchlet (Teleostei: Serranidae) from the Lord Howe Rise, Tasman Sea. 133 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 102 records from Annotated checklist of the endemic Tetrapoda species of Iran. 7 records from FIRST REPORT OF THE GENUS SESIEUTES SIMON (ARANEAE: LIOCRANIDAE) FROM CHINA, WITH DESCRIPTION OF ONE NEW SPECIES. 9 records from A new species of Carpenter Moths (Lepidoptera, Cossidae) from Tarbagatai (NE Kazakhstan) and Altai (SW Siberia, Russia) Mountains. 9 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 172533 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 2 records from Rediscovery of the holotypes of Mustela africana stolzmanni Taczanowski, 1881 (Carnivora: Mustelidae) and Cuniculus taczanowskii Stolzmann, 1885 (Rodentia: Cuniculidae) at the Museum and Institute of Zoology Polish Academy of Sciences in Warsaw, Poland. 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 141517 records from Arctic Ocean Diversity. 18 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 1 records from Archaeochiapasidae n. fam., a new early Cenomanian brachyuran family from Chiapas, Mexico, new hypothesis on Lecythocaridae Schweitzer & Feldmann, 2009, and phylogenetic implications (Crustacea, Decapoda, Brachyura, Eubrachyura). 2 records from New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece. 115 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 14 records from Five new species of the leafhopper genus Limassolla Dlabola (Hemiptera Cicadellidae: Typhlocybinae). 395 records from Données naturalistes de Jean-Michel LEMAIRE. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 652 records from Spider species diversity from wet and dry habitats. 98 records from Berkeley subregion mammals. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Two new genera, Limnohalacarus and Soldanellonyx (Acari: Halacaridae) in freshwater halacarid mites with additional new records from Turkey. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 18 records from A revision of Pinobius. II. Three new species from Cambodia and Indonesia, and additional records (Coleoptera: Staphylinidae: Paederinae). 281 records from Investigación prioritaria hacia el conocimiento y conservación de tortugas amenazadas del bosque seco tropical colombiano Mesoclemmys dahli (Carrachina) y Chelonoidis carbonaria (Morrocoy). 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 261 records from Programme ACT : Répartition Alouette lulu 2007 - 2011 Coordonnées GPS Lambert 93. 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 724 records from Invasive Alien Species in Denmark. 124 records from Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 51 records from Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 7814 records from Odonata de Veracruz. 15 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 622 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from A review of the genus Paratus Simon (Araneae, Dionycha). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 159 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 4077 records from SOPTOM_2017_12_18. 479 records from Revision of some types of North American aleocharines (Coleoptera: Staphylinidae: Aleocharinae), with synonymic notes. 1 records from A new mesoserphid wasp from the Middle Jurassic of northeastern China (Hymenoptera, Proctotrupoidea). 20 records from Happywhale - Sei Whale in South Pacific Ocean. 183 records from Oribatid mite communities (Acari: Oribatida) in different habitats of the Polistovsky Nature Reserve (Pskov Region, Russia). 941 records from Programme ACT : Répartition Pigeon ramier 1996 - 2000 Coordonnées GPS Lambert 93. 6672 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 11 records from Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records. 4 records from Benthic macrofauna abundance of sediment core 12930-017. 5 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 185 records from Inventaire des odonates d'intérêt communautaire. 477 records from Philippine Mollusk Symbiont - ICBG Collection. 5 records from Isoptera of Guam. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 6 records from The Lanternfly genus Polydictya (Hemiptera: Fulgoromorpha: Fulgoridae) from Sulawesi and neighbouring islands, with the description of three new species. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 65 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 2112 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 1798 records from Insect (KIDR-IN). 1014 records from Programme ACT : Répartition Merle noir 2009 - 2013 Coordonnées GPS Lambert 93. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from marine metagenome Metagenome. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 77 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 3 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from Morphological and molecular characterisation of Discotylenchus lorestanensis sp. n. (Nematoda: Tylenchidae) from Iran. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 118 records from Pollen profile from sediment core AV14_K2-3. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 3 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 181190 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 14502 records from Propuesta de actualización del Catálogo de Autoridades Taxonómicas (CAT) de Lepidoptera: Heterócera para la Península de Yucatán. 29876 records from European Moth Nights. 7 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6763 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New species of Heteropathes (Anthozoa: Antipatharia) expands genus distribution to the NE Atlantic. 2 records from A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 13 records from New species of Tingidae (Insecta: Heteroptera) from Madagascar. 513 records from BUND - Dassower See (Lübeck/Dassow). 58755 records from Données naturalistes de Monsieur François FOURNIER. 1727 records from TWIC Record a Raptor Survey. 21 records from Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea. 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Sächsische Schweiz (Wehlener Gebiet). 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 32 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 30 records from Revisión del género Microogenius Gutiérrez (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), con descripción de dos nuevas especies altoandinas. 2625 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 338 records from Données naturalistes de Monsieur JOURDE Rémi. 71 records from Wiesenbiotop am Wasserturm. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 20 records from A new species of sardine, Sardinella electra (Teleostei: Clupeiformes: Clupeidae), from the Ryukyu Islands, Japan. 17599 records from CAS Entomology Type (TYPE). 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 354 records from Sponges of the Guyana Shelf. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2463 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 2984 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 12308 records from MBML-Anfibios - Coleção de Anfíbios MBML. 119 records from Kinorhyncha. 19 records from Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham. 57 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 109176 records from Herps Specimens. 2923 records from Données naturalistes d'Alain BERLY. 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 37 records from COA Entomology Collection (Arctos). 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 76 records from Feriendorf des Kreises Gedern (Ober-Seemen). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 191 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 750 records from NWTRC Aerial Surveys in Puget Sound in 2016. 11 records from New species of Australopericoma Vaillant (Diptera: Psychodidae) from the Brazilian semiarid region and key to males of the genus. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 1 records from Leeuwenia hollisi sp. n. (Thysanoptera, Phlaeothripinae) from New Guinea, with the tenth abdominal segment exceptionally long. 250 records from Inventaire et regroupement de données Natura 2000. 12704 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 1 records from First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species. 21224 records from Collection Aves (bird skeletons) SMF. 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 51 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 1 records from A new species of Amolops (Anura: Ranidae) from China, with taxonomic comments on A. liangshanensis and Chinese populations of A. marmoratus. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 38 records from A new species of Elachiptera Macquart from the Galápagos Islands, Ecuador, and the taxonomic status of Ceratobarys Coquillett (Diptera: Chloropidae). 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 58 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 17 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Murciélagos). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 178 records from Corn bunting surveys on the Western Isles. 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 2 records from Charletonia Talebii N. Sp. From Iran (Acari, Prostigmata, Erythraeidae). 1 records from Bryozoa (Cyclostomata and Ctenostomata) from polymetallic nodules in the Russian exploration area, Clarion - Clipperton Fracture Zone, eastern Pacific Ocean-taxon novelty and implications of mining. 10 records from Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia. 406 records from Kimberley Islands Biodiversity Survey (Bats). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10261 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 518 records from Invasive Non-Native Species. 55 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 77 records from A survey of small mammals in the Volta Region of Ghana with comments on zoogeography and conservation. 248 records from Life cycle and production of Canuella perplexa (Copepoda, Harpacticoida) in the Sluice dock Oostende between 1976-1978. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 27 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 4 records from Herbier de Strasbourg. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 407 records from Strathclyde badger sett surveys 1996-2000. 1 records from A new species of Tungurictis Colbert, 1939 (Carnivora, Hyaenidae) from the middle Miocene of Junggar Basin, northwestern China and the early divergence of basal hyaenids in East Asia. 101 records from RISC Non-Native Species Records for Rhododendron Leafhopper. 8 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 9856 records from Spider (NSMK-SP). 3 records from MesoAmerican Reef shark habitat and environmental preferences (aggregated per 1-degree cell). 237 records from Données du/de la naturaliste Jeliazkov Aliénor provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 4 records from Happywhale - Antarctic Shag in Southern Ocean. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 36 records from Database of the European mink (Mustela lutreola L., 1761) on Kunashir Island. 27 records from The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species. 1017 records from Programme ACT : Répartition Merle noir 2003 - 2007 Coordonnées GPS Lambert 93. 29477 records from Manitoba Museum of Man and Nature. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 4 records from Sammlung Clemens Borneo Herbarium Hamburgense HBG. 15 records from Flora und Fauna im Brexbachtal. 11 records from Late Cretaceous dinosaurs from the Denver Basin, Colorado. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 3239 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from A new species of the thorid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the deep sea of the Northwestern Pacific Ocean. 6148 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 27 records from New Mixaderus species from the Mascarene Islands (Coleoptera: Aderidae). 3 records from A new, remarkable erigonine spider genus from eastern Asia (Araneae, Linyphiidae). 43 records from Homoptera, Fulgoroidea and Jassoidea of Guam. 5 records from Pollen profile II/B at Krumbach, Germany. 5 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 22136 records from Weevil and Bark Beetle records via iRecord. 209 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1737 records from Collembola of broadleaved forests along gradient of urbanization in Moscow. 238 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco (Hospederos). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 7 records from Nationalpark Harz Schul-AG Braunlage. 4 records from A new species of the genus Lamellitettigodes (Orthoptera: Tetrigidae) from PR China, with taxonomic notes on the genus. 8 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 15593 records from Skandobs. 4 records from What are the smallest moths (Lepidoptera) in the world?. 74009 records from Annelida collection of National Museum of Nature and Science. 2 records from The webspinning sawfly genus Neurotoma (Hymenoptera, Pamphiliidae) of South Korea: Neurotoma silla sp. nov. and a key to species. 1 records from A new species of Macrosaccus (Lepidoptera: Gracillariidae: Lithocolletinae) from Arizona, USA. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 55 records from Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China. 43 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 15 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 80 records from New State Stonefly (Plecoptera) Records For Pennsylvania, With Additional Records And Information On Rare Species. 1217 records from Análisis de Integridad Biológica para el Parque Natural Regional Páramo del Duende. Convenio CVC- Univalle 108 de 2017. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 4 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 26 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 82 records from Données naturalistes de Pierre-Alexis RAULT. 440 records from Wichita State University Collection. 106 records from Synopsis of the carpenter bee subgenus Xylocopa (Schonnherria) Lepeletier, 1841 (Hymenoptera: Apidae) in Colombia, with designation of lectotypes and the description of two new species. 85 records from Am Moosangerweg. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 3 records from Chemistry supports the identification of gender-specific reproductive tissue in Tyrannosaurus rex. 21 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 54 records from Stratigraphic occurrence of selected marine palynomorph species recorder in the Paleogene of ODP Hole 105-647A (Table 3). 281 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Oppia nitens. 34 records from A taxonomic revision of Otomantis Bolivar, 1890 (Mantodea: Hymenopodidae, Acromantinae) with description of five new species. 15 records from Contribution to the Chinese Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae: Rhaphidophorinae): New species of Rhaphidophora Serville, 1838 from China. 24 records from Tanzanian Vertebrate Collection. 4 records from A new species of Psyllaephagus (Hymenoptera: Encyrtidae) from China, parasitoid of Macrohomotoma sinica (Hemiptera: Homotomidae) on Ficus concinna. 2 records from A new Neotropical genus of bee flies (Diptera, Bombyliidae, Phthiriinae). 46 records from (Table 5) Distribution of foraminifera in the Miocene section of ODP Hole 133-826A. 345 records from RV Investigator Voyage IN2016_V06 Seabird Observations, Australia (2016). 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 6 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 482 records from Fossil (NSMK-FO). 409686 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 401447 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 35 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 4 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 129 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 16 records from Hazel Dormouse in Ireland. 12 records from Three new cave species of the subgenus Tachycines (Gymnaeta) (Orthoptera Rhaphidophoridae: Aemodogryllinae) from northern Guizhou, China. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 11 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 423 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2 records from Taxonomy of Oncaeidae (Copepoda, Poecilostomatoida) from the Red Sea. V. Three species of Spinoncaea gen. nov. (ivlevi-group), with notes on zoogeographical distribution. 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 33 records from An der Ohm, (Wettsaasen). 43 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 12996 records from LPO_PACA_2017_12_18. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 3 records from Two new species of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) from Brazil with a discussion on the ontogeny of leg setae. 25 records from Annotated checklist of the fishes of the archipelago of Madeira (NE Atlantic): I-Chondrichthyes. 282 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 2000 records from Observation records of Amphibians. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 38 records from HRC UNDET Aerial-Based Monitoring Surveys June 2009. 8 records from A new genus and eight new species of tail-wagger snails from eastern South Africa, with a key to genera within Sheldonia s. l. (Gastropoda: Urocyclidae). 342 records from Abundance of macroinvertebrates in sites with varying degradation levels in Lake Wamala. 7 records from Three new species of Poecilosclerida (Porifera, Demospongiae, Heteroscleromorpha) from the Aleutian Islands, Alaska. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 401 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 6241 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 11 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 8 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 8 records from On two enigmatic spiders (Araneae: Cybaeidae & Phrurolithidae) from the Russian Far East. 67 records from (UTCR) University of Tennessee - Reptiles Collection. 1490 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3470 records from Microhabitat distribution of arboreal oribatid mites (Oribatida), associated with the Siberian pine (Pinus sibirica) of Western Siberia.. 300 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 31638 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2067 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 32956 records from Collection Pisces SMF. 39872 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 7050 records from NZCS Brownsberg Nature Park Camera trap Monitoring 2013-2015. 5 records from Microbial biogeography of 925 geothermal springs in New Zealand. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 13 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 302 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 26 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 260 records from Учет следов по первому снегу (Белая тропа). 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 65 records from Landschaftspflegehof (Berlin). 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 3 records from Oratosquilla septemdentata n. sp. (Crustacea: Stomatopoda: Squillidae), a new species of deep water stomatopod from Halmahera, Indonesia. 30 records from Range table from ostracoda in ODP Hole 151-910A. 16 records from The endless search for type specimens; illustrations of eleven spider (Araneae Mygalomorphae) species described by Eugène Simon. 14567 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 35 records from Study of young rehabilitated harbour seal in the north of France (aggregated per 1-degree cell). 7 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 27898 records from UAZ Mammals. 1228 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 23 records from Viviendo en los Andes: registros notables de la distribución altitudinal del oso andino, Tremarctos ornatus (Ursidae) en Boyacá, Colombia. 1431 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 26 records from Two new tiger beetle species (Coleoptera: Cicindelidae) from Myanmar and notes on another species. 151. Contribution towards the knowledge of the Cicindelidae. 3 records from Taxonomic status of Cacoplox griseatus Hull, 1970 with redescription of the genus and type species (Diptera, Bombyliidae, Bombyliinae, Bombyliini). 200 records from Gunma Museum of Natural History, Invertebrate fossil Specimen. 72 records from Données Réseau National d’Échouages de Saint-Pierre et Miquelon. 19 records from A new species of tadpole-goby, Benthophilus persicus sp. nov. (Teleostei: Gobiidae) from the southern Caspian Sea. 336 records from Malawi-Saturniidae-Biodiversity-Data. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 12 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 303844 records from Estonian Nature Observations Database. 20 records from Phenological Center - Fishes (Arkhangelsk). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 255 records from Bird specimens of Obihiro Centennial City Museum. 17561423 records from Southern African Bird Atlas Project 2. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 97 records from Etude d'impact de la ZAC Bellevue - compléments. 6 records from Global phylogeography survey of thermophilic spores in marine sediments.. 20908 records from Seasearch Marine Surveys in the Channel Islands. 1799 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 2 records from Cosmolaelaps Berlese (Mesostigmata: Laelapidae) from southern Brazil, with a new record of a heteromorphic male, description of a new species, and a key to the species reported from that country. 328 records from Length and weight of Antarctic Rock Cod (Trematomus bernacchii) from sites adjacent to Davis Station 2012/13. 47 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 3 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 3 records from Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae Aphodiinae: Odochilini). 125 records from Resilience of Antarctic marine benthic invertebrates and the ecological consequences of environmental change - Amphipod Data 2002/10. 16 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 988 records from Hoverflies (Syrphidae) of Ireland. 143 records from Données espèces - Expertise IQE 89. 1 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 5 records from Review of the genus Microcurgus Haupt, 1950 (Hymenoptera, Pompilidae) with description of a new species from Iran. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 3105 records from South Caribbean Diversity. 2 records from A new species of the alpheid shrimp genus Automate de Man, 1888 (Decapoda: Caridea) from Japan. 6592 records from Anfibios y reptiles del estado de Tamaulipas, México. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 714 records from Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups. 1228 records from Suivis télémétriques des Otaries des Kerguelen par le Centre d'Etudes Biologiques de Chizé. 445 records from Inventory of Tragelaphus spekii in southern Benin. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 7 records from Observations on the biology of Afrotropical Hesperiidae (Lepidoptera). Part 6. Hesperiinae incertae sedis: palm feeders. 585 records from Livingstone Museum Bat Collection. 38 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 35 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 66 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 2 records from Microbial community in PAH-contaminated riverine sediments. 192 records from Traumatomutilla André miscellanea: Revision of the bellica, bifurca, diabolica, and vitelligera species groups, and a new group for the new species T. pilkingtoni Bartholomay and Williams (Hymenoptera: Mutillidae: Sphaeropthalminae: Dasymutillini). 2011 records from UNCW Right Whale Aerial Surveys 2008. 196 records from Gastropods from the Cretaceous-Palaeogene boundary in Denmark. 10965 records from Rådgivende Biologer. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 4 records from Two new species of Comesomatidae (Nematoda) from the East China Sea. 67 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 70 records from Pollen record of sediment core Bokanjacko Blato 1. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 2 records from A new species of Miobantia Giglio-Tos, 1917 with a novel morphological feature (Mantodea: Thespidae: Miobantiinae). 3558 records from Regroupement de données Odonates. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 3 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 97 records from POPA- Fisheries Observer Program of the Azores: Sea turtle sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Description of Gondwanoscurus curleri sp. nov. from the West Usambara Mts, Tanzania (Diptera: Psychodidae). 26 records from New acoustic and molecular data shed light on the poorly known Amazonian frog Adenomera simonstuarti (Leptodactylidae): implications for distribution and conservation. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 4 records from Rex, sit: digital modeling of Tyrannosaurus rex at rest. 98 records from Occurrence of mammalia relicts at site Koziarna Cave. 1 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 25 records from Happywhale - Crabeater Seal in Southern Ocean. 20 records from Review of the leafhopper tribe Macrostelini Kirkaldy (Cicadellidae: Deltocephalinae) in Pakistan with description of a new species. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 209 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 15 records from Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus. 43 records from Records Of Anacroneuria (Plecoptera: Perlidae) From Bolivia And Paraguay With Descriptions Of Three New Species. 11 records from Aktion Wiese und Wegrain Gitzenheide. 6 records from Five Newrodents From The Eastern Elburz Moitntains And A New Race Of Hare From Teheran. 2492 records from Invertebrates compiled by W.Block. 614 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 200 records from Données naturalistes de Monsieur VILAIN Frederic. 5716 records from Insect (HUNM-IN). 3032 records from Fishes in MZNA-VERT: interactions between signal crayfish and fish communities. PhD project, Iván Vedia. 86297 records from Marine Offshore Seabed Survey data held by JNCC. 82 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ciconiidae. 1694 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 1 records from The ‘‘ Lembeh Frogfish’ ’ Identified: Redescription of Nudiantennarius subteres (Smith and Radcliffe, in Radcliffe, 1912) (Teleostei: Lophiiformes: Antennariidae). 313 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1288 records from Barcant Butterfly Collection - Nymphalidae. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 258 records from Malawi-Histeridae-Biodiversity-Data. 1004 records from Données odonates. 39 records from Revision of the Hoplodrina implacata group (Lepidoptera: Noctuidae: Noctuinae: Caradrinini) of Taiwan, with descriptions of four new species. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 4 records from Two new species of Aufidus (Hemiptera, Cercopidae) from New Guinea. 24 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 61 records from The grasshoppers (Orthoptera, Acridomorpha) from the Mitaraka Mountain Range, French Guiana. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 13 records from Genus Microlithosia (Lepidoptera, Erebidae, Arctiinae) in Laos, with the description of a new species. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 7 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 8 records from Revision of Mahea Distant, 1909, with a review of the Acanthosomatidae (Insecta: Heteroptera) of Madagascar and Seychelles. 9 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 1 records from Oribates calcaratus. 470 records from arthropods on Plantago lanceolata. 6170 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from A new Scleromystax species (Siluriformes: Callichthyidae) from coastal rivers of Southern Brazil. 18 records from Happywhale - Short-finned Pilot Whale in No
Keywords: GBIF; biodiversity; species occurrences